Multiparameter Characterization of Aerosols - Babick, Frank; Hillemann, Lars; Stintz, Michael; Dillenburger, Tim; Pitz, Michael; Hellmann, Albert; Antonyuk, Sergiy; Ripperger, Siegfried; Huber, Franz; Will, Stefan; Wernet, Ruth; Seipenbusch, Martin; et al. (Chemie Ingenieur Technik, 2018)
The performance of particle-based products depends on a multiple set of particle properties. To monitor them during particle manufacturing, three novel aerosol measurement techniques were developed: wide-angle light scattering (WALS), three-dimensional laser scattering (3D-LSS), and differential aerodynamic particle sizing (DAPS). They measure particle shape, aggregate structure, and particle size, i.e., radius of gyration and aerodynamic diameter. The techniques were tested for rod-like organic pigments and partially sintered SiO2 aggregates, which were produced by two new aerosol generators.
Keywords: Aerosols; Fractal dimension; Multiparameter characterization; Particle size; Particle shape; Real-time characterization